The Effect of Compensation, Work Motivation, and Work Environment on Employee Performance Ud Gentong Racing Yogyakarta - Angraini, Ria; Puterisari, Dwi Utami (PT. Anagata Sembagi Education, 2026)
This study aims to determine the effect of Compensation, Work Motivation, and Work Environment on Employee Performance at UD Gentong Balap Yogyakarta. This study employs a quantitative research method. The population in this study consists of all employees of UD Gentong Balap Yogyakarta, totaling 30 employees. The sample was determined using the total sampling technique, meaning the entire population was used as the sample. This study uses primary data sources by distributing questionnaires directly, where respondents select from predefined answers. The analysis techniques used in this study include instrument testing, classical assumption testing, multiple linear regression analysis, F-test, t-test, correlation coefficient (R), and coefficient of determination testing. The F-test results show a significance value of 0.000 < 0.05. Thus, it can be concluded that the variables Compensation, Work Motivation, and Work Environment significantly affect Employee Performance, so the first hypothesis (H1) is accepted. Based on the t-test results, the Compensation variable has a significant value of 0.000 < 0.05, indicating that Compensation significantly affects Employee Performance, so the second hypothesis (H2) is accepted. The Work Motivation variable has a significant value of 0.000 < 0.05, indicating that Work Motivation significantly influences Employee Performance, so the third hypothesis (H3) is accepted. The Work Environment variable has a significant value of 0.024 < 0.05, indicating that Work Environment significantly influences Employee Performance, so the fourth hypothesis (H4) is accepted. The correlation coefficient (R) is 0.955, meaning there is a very strong relationship between the independent and dependent variables. The coefficient of determination (Adjusted R Square) is 0.902 (90.2%), meaning that 90.2% of the variations in Employee Performance are explained by the independent variables, while the remaining 9.8% is influenced by other variables not examined in this study.